Demographical and clinical indices for long-term evolution of patients in vegetative or in minimally conscious state - Estraneo, A; De Bellis, F; Masotta, O; Loreto, V; Fiorenza, S; Lo Sapio, M; Trojano, L (Brain injury, 2019)
Objective. To evaluate the prognostic value of demographical, anamnestic, and clinical findings on long-term outcome (up to 36 months) in individuals with severe brain injury in vegetative state (VS) or in minimally conscious state (MCS). Participants. Patients (N = 216) in VS (N = 159) or in MCS (N = 57) consecutively admitted to a neurorehabilitation unit within 1-3 months after severe anoxic (n = 71), vascular (n = 96), or traumatic (n = 49) brain injury. Main outcome. Mortality and improvements in clinical diagnosis at 12, 24, and 36 months after brain injury. Multivariable logistic regression analyses were performed to verify independent relationships of variables collected at study entry with outcome measures. Results. In patients in VS, at the 12-month follow-up, higher level of responsiveness assessed by the Coma Recovery Scale-Revised (CRS-R) total scores at study entry predicted a higher likelihood of both survival and clinical improvement, whereas younger age predicted survival only. At 24 months, female sex and higher CRS-R total scores tended to be associated with clinical improvements. In patients in MCS, younger age and female predicted consciousness recovery at 12 months. Conclusions. Several patients' features easy to collect in rehabilitation setting might help clinicians in prognostication of long-term mortality and clinical evolution of VS and MCS.